Progression of itching intensity and expression of growth factor proteins in skin of people suffering from atopic dermatitis under the influence of ultraviolet phototherapy - A. A. Kubanova; A. A. Kubanov; V. V. Chikin; V. A. Volnukhin; V. A. Smolyannikova; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Study of progression of itching intensity and expression of growth factor proteins in skin of people suffering from atopic dermatitis under the influence of narrowband (311Nm) phototherapy. Material and methods. 30 patients with atopic dermatitis were treated by using narrowband (311Nm) phototherapy. SCORAD index was used to assess the severity of the clinical responses. Itching intensity was assessed using visual analogue scale. Expression of growth factor of nerves, semaphorine-3A, amphiregulin, and PGP9.5, a protein marker for nerve fibers, was investigated by means of indirect immunofluorescence. Results. Increased expression level of nerves growth factor, decreased expression level of semaphorine-3A, and increase in the number, average length and luminous intensity of PGP9.5+ -nerve fibers were found in the patients' epidermis. Course of narrowband (311 Nm) phototherapy resulted in a decrease of the severity of the disease and itching intensity, and semaphorine-3A expression increase, reduction of number and average length of nerve fibers in the epidermis. A direct correlation relationship between the itching intensity and expression level of nerve growth factor, number and average length of PGP9.5+ -nerve fibers in the epidermis as well as an inverse correlation relationship between itching intensity and expression level of semaphorine-3A in the epidermis were found. Conclusion. Treating patients suffering from atopic dermatitis with narrowband (311 Nm) phototherapy leads to a decrease of the itching intensity associated with a decreased intensity of innervation of the epidermis. This decrease in course of phototherapy is facilitated by decrease of nerve growth factor expression level and increase of semaphorine-3A expression.